DAMPAK RESESI EKONOMI PADA PENURUNAN KEMATIAN DAN PENINGKATAN ANGKA HARAPAN HIDUP DI INDONESIA* - Siswanto Agus Wilopo (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1998)
Since July 1997, Indonesia has suffered a monetary crisis that has led to a high rate of inflation and economic recession. This situation has inflicted an impact on the individual at two levels that is through the family and then the government role. Economic recession ean also have a direct and indirect influence on the degree of public health. There is a phenomenon of epidemiological polarization, which has a bigger impact on handling public health issues during recession. Without a program and more effective and efficient activities compared with the previous years, the current economic crisis will endanger the pattern of the declining death rate and increasing life expectancy at birth. Although various studies indicate that recession and economic fluctuation does notalways lead to a stagnationand decline inpublic health, the economic conditions in Indonesia arefundamentally different from those in other countries going through a similar experience. Efforts to maintain a momentum in reducing death rate and increasing life expectancy require reinventingpublic health policy.